2017
DOI: 10.1007/s10237-017-0914-6
|View full text |Cite
|
Sign up to set email alerts
|

Capturing microscopic features of bone remodeling into a macroscopic model based on biological rationales of bone adaptation

Abstract: To understand Wolff's law, bone adaptation by remodeling at the cellular and tissue levels has been discussed extensively through experimental and simulation studies. For the clinical application of a bone remodeling simulation, it is significant to establish a macroscopic model that incorporates clarified microscopic mechanisms. In this study, we proposed novel macroscopic models based on the microscopic mechanism of osteocytic mechanosensing, in which the flow of fluid in the lacuno-canalicular porosity gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 61 publications
(65 reference statements)
0
3
0
2
Order By: Relevance
“… 45-47 In silico studies of bone metabolism have described a pathological process in which the breakdown of this feedback system due to an abnormal bone turnover balance leads to significant bone loss. 17 , 24 , 48-51 In this study, we further demonstrated that the feedback system associated with the consumptive loss of progenitors is another homeostatic mechanism that prevents rapid bone loss owing to abnormal bone turnover. Thus, our model enables a comprehensive understanding of bone metabolism, simultaneously based on the interaction across the lineage (i.e., between osteoclasts and osteoblasts) and the interaction within the lineage (i.e., between upstream progenitors and downstream differentiated cells).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“… 45-47 In silico studies of bone metabolism have described a pathological process in which the breakdown of this feedback system due to an abnormal bone turnover balance leads to significant bone loss. 17 , 24 , 48-51 In this study, we further demonstrated that the feedback system associated with the consumptive loss of progenitors is another homeostatic mechanism that prevents rapid bone loss owing to abnormal bone turnover. Thus, our model enables a comprehensive understanding of bone metabolism, simultaneously based on the interaction across the lineage (i.e., between osteoclasts and osteoblasts) and the interaction within the lineage (i.e., between upstream progenitors and downstream differentiated cells).…”
Section: Discussionmentioning
confidence: 55%
“…An FE model of the cancellous bone was constructed from X-ray micro-CT images of a swine femoral head based on a previous procedure reported by Kim et al. 24 The model was constructed as a cube of 45 × 45 × 45 voxels, and each element was a cubic voxel with an edge size of 24 μm. The bone was assumed to be a homogeneous and isotropic linear elastic material with a Young’s modulus E = 20 GPa and a Poisson’s ratio ν = 0.3.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, this model is based on the hypothesis that osteocytes regulate bone resorption and formation to achieve a locally uniform stress/strain state via bone remodeling (18,19), which means that bone remodeling is susceptible to the local spatial variation of stress/strain in the bone tissue rather than their magnitude. Considering that osteocytes in the bone matrix are believed to be stimulated by interstitial fluid flow (20), which is driven by the gradient of fluid pressure instead of the fluid pressure itself, this hypothesis would be reasonable and is validated through a theoretical study (21).…”
Section: In Silico Modeling Of Bone Remodelingmentioning
confidence: 89%
“…Шейка бедренной кости имеет неправильную форму и расширяется как при переходе в головку, так и в вертельную область. Для характеристики геометрии шейки с проксимальной и с дистальной сторон выполняли построение двух линий, параллельных ее оси (16,17), каждая из которых накладывалась на верхнюю и нижнюю поверхности в наиболее узком месте (рис. 1, ж).…”
Section: материал и методы исследованияunclassified
“…Костная ткань представляет собой опорную ткань организма и характеризуется помимо прочего способностью к постоянному обновлению внеклеточного матрикса (ремоделированию). Это возможно за счет тесного взаимодействия остеобластов, остеоцитов и остеокластов, которые обеспечивают постоянное обновление костной ткани [1,16,20]. Данный процесс направлен на адаптивную перестройку структуры костей в условиях изменения физической нагрузки, определяя реакцию скелета на деформации.…”
Section: Introductionunclassified